Fabrication and characterization of thin film ZnO Schottky contacts based UV photodetectors: A comparative study - Ali G.M.; Chakrabarti P. (My University, 2025)
The authors report on characterization of Pd/ZnO thin film Schottky contacts based UV photodetector fabricated by two methods. The ZnO film was grown on p-type Si h100i substrate by using vacuum thermal evaporation and sol-gel methods. With applied voltage in the range from -2 to +2 V we estimated the photocurrent, contrast ratio, responsivity, and quantum efficiency of the photodetectors for an incident optical power of 0.1 mW at 365 nm ultraviolet wavelength. The current-voltage characteristics were studied and the parameters such as ideality factor, leakage current, and barrier height of the Schottky contacts were extracted from the measured data. The surface morphology and the structural properties of the thin film were studied by atomic force microscope and scanning electron microscope. The bandgap of ZnO is evaluated from the absorbance spectra of ZnO thin film obtained by using double beam spectrophotometer. For the investigation of the surface chemical bonding, x-ray photoelectron spectroscopy measurements were also performed. The study revealed that sol-gel derived devices exhibit better photoresponse as compared to those using thin film deposited by vacuum deposition technique. © 2012 American Vacuum Society.